Evaluasi Penggunaan Aplikasi SITABAH BPBD Kabupaten Sumedang oleh Anggota Destana di Kecamatan Tanjungkerta - Fathurrohman Jamil; Hikmat Pramajati; Imam Tri Sutrisno (Universitas Negeri Gorontalo, 2025)
Sumedang Regency in West Java has a high level of disaster vulnerability such as landslides, floods, and tornadoes. To improve the rapid response of Disaster Management, BPBD Sumedang developed the SITABAH application as a digital platform for Disaster Information Reporting and management. However, the effectiveness of its use by the community of Desa Tangguh Bencana (DESTANA) has not been known thoroughly. This study aims to evaluate the level of use of the SITABAH application by DESTANA members in Tanjungkerta district with a descriptive quantitative approach on 85 subjects selected through convenience sampling. Research instruments referring to The Theory of Planned Behavior (TPB) include aspects of knowledge, application use, social support, and technical capabilities. The results showed that most subjects had a low level of use of SITABAH, both in frequency, feature understanding, and reporting participation. Knowledge and technical skills are also low, while social support and accessibility are in the medium category. This finding shows that SITABAH has not been optimally utilized by DESTANA members. Capacity building, continuous socialization, and technical assistance are needed to strengthen the implementation of community-based disaster systems in Sumedang Regency.